From Bust to Boom: The Great Depression and Women's Fertility - Andriana Bellou; Emanuela Cardia; Joshua Lewis (Institute of Labor Economics (IZA), 2025)
The United States experienced dramatic swings in fertility over the course of the early- and mid-20th century. This paper presents a novel explanation for these changes, linking the Great Depression to the contemporaneous fertility bust in the early 1930s, the baby boom from the late-1930s through the 1950s, and the subsequent baby bust of the 1960s. Our empirical analysis is based on an event-study approach that links county-level measures of Depression severity to annual fertility rates over an extended 50-year time horizon. We find that the Great Depression can account for roughly half of the bust-boom-bust swings in fertility rates over this period. It can also account for large cross-cohort differences in lifecycle fertility pro les and completed childbearing. We present evidence for a mechanism that accounts for these patterns: the shock incentivized Depression-era women to delay childbearing and to increase lifetime labor force participation. This employment response, in turn, temporarily crowded-out economic opportunities for subsequent generations of women, contributing to their high fertility rates through the 1950s and early 1960s.
Keywords: 330; baby boom; baby bust; Great Depression